Dara Birnbaum - reaction - Kelly, Karen J. 1964-; Schröder, Barbara (Dancing Foxes Press, 2022)
Throughout her five-decade career, New York-based artist Dara Birnbaum (born 1946) has relentlessly dissected the process of watching and has argued against the passive absorption of mass media, information and ideology, through various techniques - many of which can be described as subversive reactions or reversals. As media itself has evolved over the years, from the monolithic nature of TV broadcast networks to the Internet's decentralization of information, Birnbaum's work has remained consistently prescient and vital, incorporating new technologies and providing a touchstone for generations of younger artists. Including original scholarship by leading critics and curators of moving image and media art, this book examines Birnbaum's key works and concepts to illustrate how much her practice has to teach in a technology and media laden culture that demands constant participation and response. Exhibition: CCS Bard, Annandale-on-Hudson, USA (25.06. - 27.11.2022) / Miller Institute of Contemporary Art, Pittsburgh, USA (08.-12.2022)
Impressum: This book was published on the occasion of the exhibitions "Dara Birnbaum: Reaction", Hessel Museum of Art, Bard College, Annandale-on-Hudson, New York, June 25 - November 27, 2022. - "Dara Birnbaum: Journey", Miller Institute for Contemporary Art, Carnegie Mellon University, Pittsburgh, August 19 - November 13, 2022
Keywords: Birnbaum, Dara -- 1946-; Videokunst; Ausstellungskatalog -- Hessel Museum of Art -- 25.06.2022-27.11.2022 -- Annandale-on-Hudson, NY; Ausstellungskatalog -- Miller Institute for Contemporary Art -- 19.08.2022-13.11.2022 -- Pittsburgh, Pa.